The Benefit of Biodiversity – Polemic View of Environmental, Social and Ethical Aspects of Czech Philosophers and Environmentalists - Lípa, Jan; Rozenský, Ladislav; Ondrušák, Petr; Dolista, Josef (Studia Ecologiae et Bioethicae, 2024)
This text will deal with the issue of the benefit of biodiversity in the polemic context of the works of Czech and Central European philosophers and environmentalists with the essential ideas of selected world thinkers and with environmental practice in Central Europe. To validate this thesis, the authors of this work chose an essay dealing with professional monographs and professional articles on this topic, focusing on the continuity of ideas of the authors of the Central European region. For the comparison, forestry was used as an exemplary major field. Based on the article, the premise can be accepted that the benefit of biodiversity appears as a basic assumption, thesis, or paradigm. We need a new definition of life that is not limited to carbon-based organisms. Humankind does not live in harmony with nature but uses its culture to deplete natural resources in the false belief that man is no longer a part of nature. Environmentalists and philosophers agree on the need for a turnaround to save the environment, maintaining, biodiversity, and life on Earth. But the predatory paradigm of culture may appear to be a temporary condition and perhaps even necessary to cope with that turn. The effort to preserve biodiversity is related to the effort to preserve the life of the human species. Popularization, or environmental education, leading to biodiversity preservation and development and sustainability of life on Earth should coincide from above and below. Therefore, it could be stated that biodiversity (not only the macroscopic one) is beneficial to sustain life as we know it now.